Peristaltic Motion of Viscoelastic Fluid with Fractional Second Grade Model in Curved Channels. (23rd December 2013) - Narla, V. K.; Prasad, K. M.; Ramanamurthy, J. V.
Abstract : Exact analytic solutions are obtained for the flow of a viscoelastic fluid with fractional second grade model by peristalsis through a curved channel. The flow has been investigated under the assumptions of long wavelength and low Reynolds number approximation. The streamlines for trapped bolus of Newtonian fluid are analyzed graphically. The fractional calculus approach is used to get analytic solutions of the problem. The influence of fractional parameter, material constant, amplitude, and curvature parameter on the pressure and friction force across one wavelength are discussed numerically with the help of graphs.